Isolation and evaluation of the antioxidant actity of phenolic constituents of the Garcinia sizygiifolia - Muharni Muharni; Elfita Elfita; Didi Pratama (Universitas Jenderal Soedirman, 2017)
Garcinia sizygiifolia is a native plant to the South Sulawesi region popularly known as sula and has been cultivated in several regions in Indonesia. The plant by local community use as a food and source of wood, but has not found information on chemical content and biological activity. Therefore, this study was carried out to Isolation and evaluation of the antioxidant activity of the phenolic constituent of the G. sizygiifolia. A 30.0 g portion of ethyl acetate extract of the stembark G. sizygiifolia were separated by column chromatography method using silica G 60 F254 (230-400 mesh), eluted gradient polarity mixtures of n-hexane-ethyl acetate were collected and sorted into fractions. Fraction F 1 (5.2 g) were separated and purified again by chromatography method until pure compound obtained. The structure of the isolated compound was determined using UV, IR, and NMR spectroscopy. The antioxidant activity was tested by DPPH method. The isolated pure compound was a yellow solid with melting point 148-149 oC. Base on spectroscopy data and by comparison with data from the literature, isolated compound is a known compound 2,4-dihydroxyphenylethanone. The compound exhibited antioxidant activity with IC50 96 µg/mL against DPPH.